(untitled) (Research, Society and Development, 2020)
Youth and Adult Education (EJA) is aimed at teaching individuals who were unable to study and complete elementary and / or secondary education at the correct time and at the appropriate age. Taken by the need to adapt to the job market, in addition to the desire to complete their studies and acquire knowledge, EJA students are usually individuals with a profile of workers from the popular social strata. The objective of this research was to analyze the profile of students of Youth and Adult Education (EJA) in Macapá AP in 2018. The quantitative and qualitative research was carried out with EJA students. Women tend to give up regular education because of family or children. Social inequality means that, as far as ethnicity is concerned, pardos and blacks finish their studies over time, at EJA. Students are increasingly younger. The degree of educational background of the individual is directly proportional to the remuneration received by the individual.